2020
DOI: 10.18103/mra.v8i11.2283
|View full text |Cite
|
Sign up to set email alerts
|

Current Use of Calcium Sulfate Bone Grafts

Abstract: Bone graft placement is the most widely used therapeutic strategy for the surgical correction of osseous defects. In recent years, increasing attention has been given to the development of synthetic bone grafts. Of those currently available, calcium sulfate materials exhibit several unique properties that warrant discussion. These include their intrinsic osteogenic potential, their stimulatory effect on angiogenesis, the fact that they are fully biodegradable, the lack of proinflammatory responses following th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…45 However, the growth rate of new bone is much less than the resorptive rate of calcium sulfate material in vivo, resulting in delayed bone healing, which is the most cited limitation of the clinical application of calcium sulfate bone cement. 59,60 Calcium phosphate bone cement (CPC) has satisfactory biocompatibility, osteoconductivity, osteoinductivity, and in particular, since CPC has a suitable rate of degradation, releasing calcium and phosphorus ions to induce bone formation. 61 In addition, calcium phosphate bone cement can self-cure under physiological conditions to form hydroxyapatite similar to the inorganic composition of human bone tissue, with little heat released during curing, and does not cause inflammatory reactions after implantation.…”
Section: Biological Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…45 However, the growth rate of new bone is much less than the resorptive rate of calcium sulfate material in vivo, resulting in delayed bone healing, which is the most cited limitation of the clinical application of calcium sulfate bone cement. 59,60 Calcium phosphate bone cement (CPC) has satisfactory biocompatibility, osteoconductivity, osteoinductivity, and in particular, since CPC has a suitable rate of degradation, releasing calcium and phosphorus ions to induce bone formation. 61 In addition, calcium phosphate bone cement can self-cure under physiological conditions to form hydroxyapatite similar to the inorganic composition of human bone tissue, with little heat released during curing, and does not cause inflammatory reactions after implantation.…”
Section: Biological Materialsmentioning
confidence: 99%
“…Kim et al reported the application of AlloMatrix which is an allogenic DBM product that serves as a carrier of calcium sulfate in the dental field to guide bone regeneration; the osteoinductive effect of this allogenic graft material is proven by the clinical evaluation and histological tests of new bone formation . However, the growth rate of new bone is much less than the resorptive rate of calcium sulfate material in vivo, resulting in delayed bone healing, which is the most cited limitation of the clinical application of calcium sulfate bone cement. , Calcium phosphate bone cement (CPC) has satisfactory biocompatibility, osteoconductivity, osteoinductivity, and in particular, since CPC has a suitable rate of degradation, releasing calcium and phosphorus ions to induce bone formation . In addition, calcium phosphate bone cement can self-cure under physiological conditions to form hydroxyapatite similar to the inorganic composition of human bone tissue, with little heat released during curing, and does not cause inflammatory reactions after implantation. Besides, as highlighted by Cuylear et al in a recent review, the application of CaP particles as drug delivery systems for regeneration and biomineralization of craniofacial bone has garnered extensive interest these years due to their tunability and facile loading of therapeutic agents such as small molecules, genes, proteins, and peptides .…”
Section: Biological Materialsmentioning
confidence: 99%
“…Degradable materials such as bioceramics are alternatives to avoid donor site injury and superior for bone repairs due to their improved biocompatibility, osteoconductivity, consistent material properties, and low cost. Among them, calcium sulfate (CS) and calcium phosphate (CaP) have demonstrated the ability to partially integrate into bone tissue and stimulate osteoblast growth and have been widely used in the place of allografts or autografts for several decades [ 4 , 5 , 6 , 7 , 8 , 9 ]. CS possesses several desirable properties including a low curing temperature, rapid setting, biocompatibility, biodegradability, and promotion of bone healing.…”
Section: Introductionmentioning
confidence: 99%
“…This filler exhibits good injectability, biocompatibility, osteoconductivity, biodegradability, rapid, and complete resorption, with a minor inflammatory reaction in the human body 3–5 . Moreover, the stimulatory effect of calcium sulfate on angiogenesis could enhance bone regeneration process 6 . Furthermore, this injectable, minimally invasive bone‐void filler can fill the bony defects and set in situ, which facilitates its clinical applications 7 .…”
Section: Introductionmentioning
confidence: 99%